RS-1 enhances CRISPR/Cas9- and TALEN-mediated knock-in efficiency - Jun Song; Dongshan Yang; Jie Xu; Tianqing Zhu; Y. Eugene Chen; Jifeng Zhang (Nature Communications, 2016)
CRISPR/Cas9 and transcription activator-like effector nuclease (TALEN) are becoming major tools for genome editing. Here, Song et al. show that RS-1, a small-molecule enhancer for homology directed repair, increases the CRISPR/Cas9 and TALEN mediated knock-in efficiency both in vitro and in vivowith rabbit.